GR_GERICHTE SKA 2002 28 vom 3. Dezember 2002 , Verwertungsbegehren - GR Gerichte (2002)
Lohnpfändung/Anzeige an Arbeitgeber | Leitentscheid, publiziert als PKG 2002 30\x3Cbr\x3E | Beschwerde 17 Abs. 1 SchKG